The Influence of Organizational Culture, Internal Environment and Leadership Style on Employee Performance at PT. Rubber Hock Lie Sunggal - Adriani Rangkuti, Dhita; Riandi Hutagalung, Risky; Permadi Tarihoran, Didi; Larisa Gobel, Vania; Yanti Zebua, Warni (International Journal of Educational Research & Social Sciences, 2022)
This study aims to understand the influence of organizational culture, internal environment and leadership style on employee performance at PT.Rubber Hock Lie Sunggal. The research method uses descriptive quantitative, the population in this study consisted of 166 people. This sampling used the purposive sampling technique with the Slovin formula as a measuring tool to calculate the sample with a general level of 5% used, so that this study amounted to 117 populations. In this study using multiple linear regression method. The results of this study answered the research hypothesis and the results of R square 33.6%.